A new species of the genus Paulianidia Jarrige and a new combination in Pseudolathra Casey (Coleoptera, Staphylinidae, Paederinae) - Koszela, Katarzyna; Sarmiento, Yoan Camilo Guzman; Żyła, Dagmara (Zootaxa, 2023)
The genus Paulianidia (Coleoptera, Staphylinidae, Paederinae) was described by Jarrige, 1978 and thus far, it consists of 24 species. It is endemic to Madagascar and has been sampled in the leaf litter layer of soil in mountainous regions with little sign of degradation. Here, we describe a new species in the genus, Paulianidia parahammondi sp. nov., and compare it with its supposedly closest relative. We provide an updated key to all Paulianidia species and an updated genus description. We also discuss the systematic position of Paulianidia, and provide characters for distinguishing it from other Paederinae of Madagascar. Additionally, the Paederinae species Lathrobium catenulatum Fauvel, 1905 is transferred here to Pseudolathra Casey, 1905 as P. catenulata (Fauvel, 1905) comb. nov.